1996
DOI: 10.1021/ic9511128
|View full text |Cite
|
Sign up to set email alerts
|

1-Phenyl-1,2-dicarba-closo-dodecaborane, 1-Ph-1,2-closo-C2B10H11. Synthesis, Characterization, and Structure As Determined in the Gas Phase by Electron Diffraction, in the Crystalline Phase at 199 K by X-ray Diffraction, and by ab Initio Computations

Abstract: The compound 1-phenyl-1,2-dicarba-closo-dodecaborane(12), 1-C(6)H(5)-1,2-closo-C(2)B(10)H(11) (1), has been synthesized and characterized by a complete assignment of its (11)B NMR spectrum via (11)B{(1)H}/(11)B{(1)H} (COSY), (1)H{(11)B(selective)} and (1)H{(11)B}/(1)H{(11)B} (COSY) spectroscopy. An electron- and X-ray diffraction investigation of 1, complemented by ab initio calculations, has been undertaken. The gas-phase electron-diffraction (GED) data can be fitted by several models describing conformations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 37 publications
7
13
0
Order By: Relevance
“…24,25 This was further explored by ab initio RHF/6-31G* and MP2/6-31G* calculational studies on 1-phenylortho-carborane and other aryl-carboranes in order to probe the orientational preferences of aryl groups attached to the carbon atoms of ortho-carborane. 26,27 These calculations have indicated that, although the overall energy of an aryl-carborane may vary only slightly with the aryl group orientation, the latter does have a perceptible influence on the C(1)-C(2) bond distance, which is greatest when the aryl group is aligned perpendicular to the aryl C-C(1)-C(2) plane. This is because this orientation optimises transfer of electronic charge from the filled π orbitals of the aryl group into a cage LUMO that is σ-antibonding with respect to the cage bond C(1)-C(2).…”
Section: Structural Aspectsmentioning
confidence: 99%
“…24,25 This was further explored by ab initio RHF/6-31G* and MP2/6-31G* calculational studies on 1-phenylortho-carborane and other aryl-carboranes in order to probe the orientational preferences of aryl groups attached to the carbon atoms of ortho-carborane. 26,27 These calculations have indicated that, although the overall energy of an aryl-carborane may vary only slightly with the aryl group orientation, the latter does have a perceptible influence on the C(1)-C(2) bond distance, which is greatest when the aryl group is aligned perpendicular to the aryl C-C(1)-C(2) plane. This is because this orientation optimises transfer of electronic charge from the filled π orbitals of the aryl group into a cage LUMO that is σ-antibonding with respect to the cage bond C(1)-C(2).…”
Section: Structural Aspectsmentioning
confidence: 99%
“…According to the theoretical and experimental studies, the replacement of CH by a CPh group in the o ‐carborane has a small electronic influence on the cage, but results in significant steric changes in the molecule due to H ··· H contacts 1. It was found that in the isolated molecule 1 , there is an optimum value of the torsion angle θ [C(2)−C(1)−C(13)−C(14)], equal to 25°,9 defining the conformation of the ring with respect to the carborane cage (see Figure 1). Although the H ··· H contacts in all conformations are substantially shorter than the sum of the van der Waals radii the barrier to rotation of the phenyl ring according to the HF/6−31G* calculations is very small (2.1 kJ·mol −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Deuterated solvents were stored over 4 Å molecular sieves. [1-PPh 2 - closo -1,2-C 2 B 10 H 11 ] ( IVa ) [28], [1-P i Pr 2 - closo -1,2-C 2 B 10 H 11 ] ( IVb ) [29], [1-P t Bu 2 - closo -1,2-C 2 B 10 H 11 ] ( IVc ) [30], [9-PPh 2 - closo -1,7-C 2 B 10 H 11 ] ( V ) [13], [μ-2,2′-PPh-{1-(1′-1′,2′- closo -C 2 B 10 H 10 )-1,2- closo -C 2 B 10 H 10 }] ( IX ) [24], and [1-Ph- closo -1,2-C 2 B 10 H 11 ] [31,32] were prepared according to the literature. All other reagents were purchased from Sigma Aldrich Ltd. (Gillingham, UK), Fluorochem Ltd. (Hadfield, UK) or Alfa Aesar (Heysham, UK) and used without further purification.…”
Section: Methodsmentioning
confidence: 99%